PENDIDIKAN ANAK USIA DINI BERBASIS LIFE SKILLS - Dyah Nugrahani; Senowarsito IKIP PGRI Semarang; Ngasbun Egar; Listyaning Sumardiyani; Subur L Wardoyo (E-Dimas: Jurnal Pengabdian kepada Masyarakat, 2011)
Abstract To achieve the goal of teaching learning, a proper method, as an instrument, plays an important role in serving the teaching learning materials. The education of pre-school is aimed to develop the life skill, which covers attitude, knowledge, creativity, and skill. The teaching learning methode that forms the child?óÔé¼Ôäós character has to be turned back to the curriculum. It should remain concerning in the phase of the development and character of child who like playing, singing, dan moving. Finally, the teaching learning methode must be addressed in shaping academic, social, personal intellegence, and child?óÔé¼Ôäós creativity. Key words: a proper method, pre-school, life skills